Use of strategies to improve retention in primary care randomised trials: a qualitative study with in-depth interviews. Issue 1 (24th January 2014) - Brueton, V C; Stevenson, F; Vale, C L; Stenning, S P; Tierney, J F; Harding, S; Nazareth, I; Meredith, S; Rait, G
Abstract : Objective: To explore the strategies used to improve retention in primary care randomised trials. Design: Qualitative in-depth interviews and thematic analysis. Participants: 29 UK primary care chief and principal investigators, trial managers and research nurses. Methods: In-depth face-to-face interviews. Results: Primary care researchers use incentive and communication strategies to improve retention in trials, but were unsure of their effect. Small monetary incentives were used to increase response to postal questionnaires. Non-monetary incentives were used although there was scepticism about the impact of these on retention. Nurses routinely used telephone communication to encourage participants to return for trial follow-up. Trial managers used first class post, shorter questionnaires and improved questionnaire designs with the aim of improving questionnaire response. Interviewees thought an open trial design could lead to biased results and were negative about using behavioural strategies to improve retention. There was consensus among the interviewees that effective communication and rapport with participants, participant altruism, respect for participant's time, flexibility of trial personnel and appointment schedules and trial information improve retention. Interviewees noted particular challenges with retention in mental health trials and those involving teenagers. Conclusions: The findings of this qualitative study have allowed us to reflect on research practice around retention and highlight a gap between such practice and current evidence. Interviewees describe acting from experience without evidence from the literature, which supports the use of small monetary incentives to improve the questionnaire response. No such evidence exists for non-monetary incentives or first class post, use of which may need reconsideration. An exploration of barriers and facilitators to retention in other research contexts may be justified.